Case Report: Loss-of-Function ABCC9 Genetic Variant Associated With Ventricular Fibrillation - Zaytseva, Anastasia; Tulintseva, Tatyana; Fomicheva, Yulya; Mikhailova, Valeria; Treshkur, Tatiana; Kostareva, Anna (Frontiers in Genetics, 2022)
Genetic variants in ABCC9 gene, encoding SUR2 auxiliary subunit from KATP channels, were previously linked with various inherited diseases. This wide range of congenital disorders includes multisystem and cardiovascular pathologies. Thus, gain-of-function mutations result in Cantu syndrome, acromegaloid facial appearance, hypertrichosis, and acromegaloid facial features. Loss-of-function mutations in the ABCC9 were associated with Brugada syndrome, early repolarization syndrome, and dilated cardiomyopathy. Here, we report a patient with loss-of-function variant in the ABCC9 gene, identified by target high-throughput sequencing. The female proband presented with several episodes of ventricular fibrillation and hypokalemia upon emotional stress. This case shed light on the consequences of KATP channels dysfunction in the cardiovascular system and underlined the complexity of the clinical presentation of ABCC9-related diseases.